Kebijakan Pemidanaan dalam KUHP Baru Indonesia: Antara Humanisasi dan Represivitas (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2026)
This study aims to map the direction of criminal punishment policy formulated in criminal law provisions, test claims of humanizing punishment through sanction design and the principle of individualization, and describe forms of repression that operate through normative flexibility, law enforcement discretion, and morally nuanced criminalization. The research method used is normative legal research, utilizing both a legislative and conceptual approach to analyze the norms, principles, and objectives of punishment. The results show that Article 51 articulates the objectives of punishment, including the rehabilitation of offenders, community protection, and the restoration of social balance. However, this provision functions primarily as normative legitimacy for a flexible sanction architecture. The existence of alternative punishments and oversight mechanisms refines the form of punishment while expanding state intervention into the social life of offenders. Furthermore, the regulation of conditional sentences and adjustments to the implementation of sanctions increase the discretion of law enforcement officials. Repression does not disappear, but rather shifts through regulations on morality, public order, recognition of living law, and the threat of symbolic punishment, shifting the relationship between the state and individuals toward ongoing administrative control.